Stroboscopic Surface Thermal Lensing for Fast Detection of Thermal Defects in Large-Scaled Coating Films - Chunxian Tao; Dawei Zhang; Ruijin Hong; Zhongfei Wang (The Scientific World Journal)
A stroboscopic surface thermal lensing (SSTL) system for the fast detection of thermal-induced defects in large-scaled optical coating films was constructed. The SSTL signal was generated by a set of double-modulators and captured by a high speed matrix camera, respectively. The spot size of both pump laser and probe laser expanded for larger detection area was finished in a single step. Based on the STL technique, both the mapping of amplitude and the phase of SSTL signal on the whole area of the coatings can be achieved simultaneously.